Governance Issues and Deep-Rooted Corruption in Pakistan - Dawood Nawaz, Shahbaz Ali Khan, Sarfraz Batool, Arsalan Rasool (International Journal of Modern Agriculture, 2021)
The concept of governance is based on lessons from history which records both the downfall of nations resulting from bad governance, and also lessons of how nations have risen to great heights as a consequence of good governance. Good governance is the prerequisite for human development. The objective of governance in any society is a social development as well as economic growth and prosperity. Good governance can be seen as the participation of all stakeholders in the political system, leadership, consensus-based decision making, rule of law and justice, transparency in policies and procedure, surety of equity, responsiveness to problems, overall work effectiveness and efficiency, unbiased accountability and a stable economy. Therefore, transparency and accountability have vital roles to play in building good governance, since good governance is believed to be free and immune from corruption and social injustice. The objective of this study is to identify and analyze the issues and challenges of governance and good governance which are the main hurdle in the way of development in Pakistan. This study is a qualitative in nature. The researchers have used the data through secondary sources such as research articles and books. There is a great need to give the special attention towards the utilization of the potential resources for public, civil society groups to perform an active and equal participation in the governmental affairs, and held accountable to the government and political parties for their usage of public resources.